2016
DOI: 10.1371/journal.pntd.0004919
|View full text |Cite
|
Sign up to set email alerts
|

Community Involvement in Dengue Outbreak Control: An Integrated Rigorous Intervention Strategy

Abstract: BackgroundAn explosive outbreak of dengue fever occurred in Guangdong Province, China in 2014. A community-based integrated intervention was applied to control this outbreak in the capital city Guangzhou, where dengue epidemic was mainly caused by imported cases.Methodology/Principal FindingsWe used a time series generalized additive model based on meteorological factors to assess the effectiveness of this intervention. The results showed that there was significant reduction in mosquito density following the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 22 publications
2
30
1
1
Order By: Relevance
“…It is a great concern in many other countries. 14,15,19,36,38,39 In our study context, health staff or people from mass organizations and relevant stakeholders normally had a low basic wage. They would not receive more allowance even if work harder to fulfill their tasks in the dengue vector control program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a great concern in many other countries. 14,15,19,36,38,39 In our study context, health staff or people from mass organizations and relevant stakeholders normally had a low basic wage. They would not receive more allowance even if work harder to fulfill their tasks in the dengue vector control program.…”
Section: Discussionmentioning
confidence: 99%
“…12 There has been an increasing trend of community-based participatory interventions using integrated community engagement strategies in the recent decades. [13][14][15][16][17] However, findings from a systematic review indicated that the evidencebased community engagement in dengue vector control programs was still weak. 18 Also, multi-entity coordination and partnership between relevant stakeholders in most dengue programs have been limited.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, dengue occurred in a few provinces in Southern China, although at a relatively low rate. Suddenly in 2014, Guangdong experienced a large outbreak with 45 224 cases [73].…”
Section: Re-emerging Infectious Diseasesmentioning
confidence: 99%
“…The key measure for preventing the transmission continues to be vector control since no effective vaccine and no specific treatment are available (WHO, 2009). However, vector control methods have often a limited success rate, not only because of increasing insecticide resistance where chemical methods are used (Nathan, 2013;Barrera, 2016;), but also because of the lack of community participation and the unsustainability of resource intensive vector control in some countries (Lin et al, 2016). The need to prevent the diseases has resulted in new technological innovations including the use of drones with cameras to identify breeding places, computing systems for monitoring and tracking high transmission areas, case tracking of index cases, software for epidemiological surveys and mobile devices for communication and networking (Boger and Low, 2016;Sood and Mahajan, 2017; Sareen et al, 2017; de Souza Silva et al, 2018).…”
Section: Introductionmentioning
confidence: 99%